Difficulties in Treating Ethnic Minority Children with ADHD and the Role of Mobile Applications - Doulou, Aikaterini; Drigas, Athanasios; Skianis, Charalampos (International Journal of Interactive Mobile Technologies (iJIM), 2023)
There is proof that kids and teens from ethnic minorities get less health care than theirnon-minority peers, despite the fact that Attention Deficit Hyperactivity Disorder (ADHD) ismore common in these populations. Minority children might not receive timely, adequateADHD intervention because of the low socioeconomic position of minority parents, their lackof awareness regarding ADHD, and the available remedial techniques. People are looking tothe digital world for answers to challenges in their daily lives as the number of mobile applicationsgrows. People with impairments now have equal access to learning opportunitiesbecause to technological advancements. The majority of their time is now spent on mobiledevices by kids. As a result, using mobile applications to solve their problems would be quitesuccessful. Mobile learning, also known as e-learning programs that utilize mobile devices,can be employed as a form of therapy to enhance both executive functioning and generalwell-being. Also, by practicing cognitive and metacognitive task abilities more frequently, theyincrease motivation in kids and teenagers. Also, the understanding and retention of the presentedinformation might be aided by the audiovisual stimuli offered through smartphoneapplications. They may therefore serve as crucial learning aids for kids with ADHD. The currentstudy examines the function and efficacy of mobile applications in enhancing the qualityof life of children from ethnic minorities who have Attention Deficit Hyperactivity Disorder(ADHD), as well as the barriers that may impede or delay their access to treatment services.